L’administration Eisenhower et la vente d’armes à La Havane - Salim Lamrani (Études Caribéennes)
Following the advent of the Cuban Revolution in 1959, the United States opposed the program of socio-economic transformation undertaken by the new authorities and adopted a hostile policy. Far from fearing a rapprochement between Havana and Moscow, Washington on the contrary deliberately pushed the island towards the Soviet Union, in order to be able to justify the drastic measures that the Eisenhower administration was preparing to adopt against Cuba, namely the economic sanctions and the isolation of the country. The episode of the sale of arms is illustrative of this desire to force Fidel Castro to seek help from the socialist bloc.